Exploring the utility of an indel-rich, mitochondrial intergenic region as a molecular barcode for bamboo corals (Octocorallia: Isididae) - van der Ham, Joris L.; Brugler, Mercer R.; France, Scott C. (Marine genomics, 2009)
The DNA barcoding initiative has advocated the use of the 5′-end (∼ 658 bp) of mitochondrial (mt) cytochrome c oxidase subunit 1 ( cox1) to genetically distinguish species. However, this has proven difficult within the subclass Octocorallia due to extraordinarily low substitution rates within mt protein-coding genes. Intergenic regions (IGRs), which have been little examined among octocorals, may be subject to high mutation rates and have proven useful target regions at both the interspecific and population levels of metazoans. Herein we examine a mt IGR ( igr4) between the cytochrome b ( cob) and NADH dehydrogenase subunit 6 ( nad6) genes among species of the bamboo coral subfamily Keratoisidinae to evaluate its utility for barcoding and phylogenetic studies. Among 77 keratoisidin specimens, we found igr4 to vary in length between either 42 bp ( Acanella Gray, 1870 and Orstomisis Bayer, 1990) or 302–605 bp ( Isidella Gray, 1857 , Lepidisis Verrill, 1883, Keratoisis Wright, 1869 , and two undescribed genera). We interpreted the short igr4 sequence of Acanella eburnea (Pourtalès, 1868) as potentially indicative of additional mt genome-related novelties and thus sequenced its entire mt genome; gene content and gene order were the same as in a previously-sequenced bamboo coral mt genome. Alignment of the longer igr4 sequences included 108 parsimony-informative characters, as well as numerous indels ranging from 2–262 bp in length. Uncorrected pairwise ‘ p’ distances indicated sequence variation of 0–27.2%, as compared to 0–4.8% among the same specimens for the MutS homolog ( msh1), currently the most widely sequenced octocorallian mt gene, and <0.4% for cox1 for a subset of the taxa. Despite the greater levels of variation, fewer unique haplotypes were observed at igr4 compared to msh1; however, in combination, the two gene regions revealed increased mt haplotype diversity relative to either gene region on their own.